COVID-19 and global poverty: Are LDCs being left behind? - Giovanni Valensisi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper provides a preliminary assessment of COVID-19's impact on global poverty in the light of the IMF's April 2020 growth forecasts. The analysis shows that the pandemic will have dramatic consequences, eroding many of the gains recorded over the last decade in terms of poverty reduction. Our baseline case suggests that globally the number of people living below US1.90 per day could increase by 68 million in 2020 alone, with much larger effects should the recession turn out to be more severe than expected. This represents a significant setback and, without effective international support and cooperation, will pose a critical threat to the achievement of the United Nations 2030 Agenda for Sustainable Development. The fallout from the pandemic will also exacerbate the geographic concentration of poverty, as exemplified by the case of the Least Developed Countries, which are set to represent the main locus of extreme poverty.
Keywords: I32; O15; N30; 330; COVID-19; crisis impact; global poverty; Least Developed Countries; SDGs